USE OF BAGS AS CHARCOAL BRICKETS AS A WASTE SOLUTION IN LANGSA CITY IN ALUE DUA VILLAGE, LANGSA BARO DISTRICT, LANGSA CITY - Faoeza Hafiz Saragih; Haikal Fajri; Defri Basrin (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
There is quite a lot of sugarcane bagasse waste in Langsa City which is not utilized properly and only ends up in the city landfill. This sugarcane bagasse waste can be processed and utilized into a high-value product, namely charcoal briquettes. Where currently the demand for energy sources that are environmentally friendly and have affordable prices is very popular with the public both at home and abroad. Therefore, to reduce sugarcane bagasse waste and make it of high economic value, training was held on making charcoal briquettes from bagasse and improving the community's economy. This service activity will be carried out in Alue Dua Village, Langsa Baro District. The output of this activity is the creation of briquette charcoal products and increasing partner income. The results achieved in this activity were to increase the partners' insight into processing sugarcane bagasse into charcoal briquettes. In the future, partners also hope that there will be training related to digital marketing for the products they produce.